Satisfaction of Health Educator Nurses through an Ongoing Professional Education Program Using Two Instructional Methods - Amer H. Al-Shehri; Marwan Abu Hijleh (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of the study was to determine whether the interactive teaching method is more effective than the lecture-based method with regard to the nurse educator’s satisfaction and learning. No local study has been conducted in this area in health educational training programs in the primary health care setting. The study was conducted between January and June 2008 in the Dammam area of the Kingdom of Saudi Arabia. The study was a cross-sectional study that sought to identify the perceptions of health educator nurses; of the 40 invited to participate, 34 nurse educators from 20 primary health care centers attended. They were subjected to the traditional lecture-based method of instruction, after which participants’ perception was registered. One month later, each group attended another session which used the interactive teaching method with peer teaching, and then their perception was registered. There was a statistically significant difference between the traditional and interactive methods in 10 items out of the 22-item questionnaire (higher scores toward interactive method). Nurse educators in primary health care centers prefer an interactive teaching method and peer teaching over the traditional lecture-based method of instruction.